Streptokinase treatment of a thrombosed Björk-Shiley prosthesis in the aortic position. Issue 6 (June 1992) - Mehan, V K; Dalvi, B V; Kale, P A
Abstract : Dysfunction of a mechanical prosthetic valve caused by thrombus formation is usually treated surgically. A patient with a thrombosed Björk-Shiley valve in the aortic position was treated successfully with intravenous streptokinase. The considerable improvement in the patient's clinical condition and the phonocardiographic, echocardiographic, and cinefluoroscopic evidence of normalisation of prosthetic valve function established the efficacy of thrombolytic therapy of a thrombosed prosthetic valve in this patient.